A Disciplined Brand Approach to Marketing Libraries - Spenser Thompson (Marketing Libraries Journal, 2018)
The purpose of this paper is to propose a narrow definition of brand, explain why it is important, and present practical exercises to discover a library’s brand. Based on the author’s experience in corporate and library settings, a brand is defined as an idea that can be discovered by two formal processes outlined in the paper. Libraries can use branding to create more focused marketing programs—going beyond logos or claims about services—that, in turn, will have a greater impact on potential users. The processes described in this article provide an alternative to costly and time-consuming consultants or agencies. Furthermore, these two templates for brand discovery enable librarians to move beyond marketing libraries generically to marketing a specific library. This article discusses organizational culture and related obstacles to brand discovery and implementation.